Differences in praxis performance and receptive language during fingerspelling between deaf children with and without autism spectrum disorder. (April 2018) - Bhat, Anjana N; Srinivasan, Sudha M; Woxholdt, Colleen; Shield, Aaron
Children with autism spectrum disorder present with a variety of social communication deficits such as atypicalities in social gaze and verbal and non-verbal communication delays as well as perceptuo-motor deficits like motor incoordination and dyspraxia. In this study, we had the unique opportunity to study praxis performance in deaf children with and without autism spectrum disorder in a fingerspelling context using American Sign Language. A total of 11 deaf children with autism spectrum disorder and 11 typically developing deaf children aged between 5 and 14 years completed a fingerspelling task. Children were asked to fingerspell 15 different words shown on an iPad. We coded various praxis errors and fingerspelling time. The deaf children with autism spectrum disorder had greater errors in pace, sequence precision, accuracy, and body part use and also took longer to fingerspell each word. Additionally, the deaf children with autism spectrum disorder had poor receptive language skills and this strongly correlated with their praxis performance and autism severity. These findings extend the evidence for dyspraxia in hearing children with autism spectrum disorder to deaf children with autism spectrum disorder. Poor sign language production in children with autism spectrum disorder may contribute to their poor gestural learning/comprehension and vice versa. Our findings have therapeutic implications for children with autism spectrum disorder when teaching sign language.